Integration of Argo Binangun Tourism Awareness Group and Geotourism: Sustainable Development of Widosari Tourism Village, Yogyakarta - Pudji Muljono; Ence Oos Mukhamad Anwas; sasongko, yohanes probo; Siti Amanah (Jurnal Antropologi: Isu-Isu Sosial Budaya, 2025)
The role of stakeholder synergy in developing geotourism-based tourist attractions is an urgent matter that can be realized. The low level of cooperation between stakeholders in the Widosari tourist village can be seen in several notes, such as the suboptimal construction of roads that are used as a means to get to tourist locations, the suboptimal construction of facilities at the tourist attraction, the suboptimal number of workers at the tourist location are important notes so that stakeholder collaboration can be realized immediately. Research that is studied qualitatively by presenting stakeholder theory can be a bridge to build comprehensive cooperation. Collaboration between stakeholders is the pillars of realizing sustainable tourism development, especially in the nature-based tourism sector. Sustainable planning in the Widosari Tourist Village is a form of optimal environmental communication development, because it involves all existing components, both the community, government, private parties and Pokdarwis itself. The results of research conducted using the utilization of a number of synergistic institutions can be a significant solution that the Widosari Tourist Village has great potential that can be developed comprehensively.